Flipped Classroom, Flipped Teaching and Flipped Learning in the Foreign/Second Language Post–Secondary Classroom - Mohan, Denise (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2018)
The term “flipped classroom”, coined in 2007, represents a pedagogy aligned with long-established principles of student-centered learning. Over the last two decades, the flipped classroom has been adopted by instructors across a range of disciplines, from primary to post-secondary settings. During its development, the characteristics of the flipped classroom have evolved, as have the terminology used to reference it, leading practitioners and researchers to now address it as flipped classroom, flipped teaching or flipped learning. In this article, these terms will be used interchangeably. The article will examine the foundations of flipped learning, discuss its roots in learner-centered pedagogy, trace its development over the last two decades, profile its characteristics, and examine the feedback on its effectiveness and challenges as provided by flipped learning instructors and researchers. An attempt will be made to answer the following four questions. Where does flipped learning fit on the continuum of learner-centered pedagogies? How have educators responded, both positively and negatively, to the flipped learning/teaching approach? How has flipped learning been implemented in the foreign/second language (FL/L2) classroom? What are some considerations and recommendations for FL/L2 instructors contemplating using this approach in the FL/L2 post-secondary context? Finally, some suggestions will be made regarding next steps in research on flipped learning.